ҒӘРЕЗСИЗЛИК ЖЫЛЛАРЫНДА МӘМЛЕКЕТИМИЗДЕ АГРАР ТАРАЎЫНДАҒЫ КАДРЛАР ТАЯРЛАЎ МӘСЕЛЕСИ (1991-2020) - Төрениязова, Г.Е. (SCIENCE and SOCIETY, 2025)
This article outlines the achievements in the field of agricultural higher education in the Republic of Uzbekistan and the Republic of Karakalpakstan, as well as several directions for the reorganization of higher educational institutions in the agricultural sector.